Repression and Resistance in Fatima Bhutto’s The Shadow of the Crescent Moon - Farhan , Mohiodin; Nawaz, Shazmeen; Najam, Maria (Pakistan Journal of Humanities and Social Sciences, 2023)
This paper aims at discovering factors that play vital role in the alienation and marginalization of masses by ‘State Apparatuses’ that not only compel them to show unwavering obedience to state but also force them to sacrifice their right to freedom and will. It will spotlight some modes in which suppressed people resist against state apparatuses in order to secure their freedom. The aim of this research is to provide a platform to those silent voices or lost groups which have never been represented in the state narratives. Discussing the socio-political scenario of Federally Administrated Tribal Area, this work speaks the unspeakable things via deconstructing the bitter facts about the particular region: Mir Ali. Bhutto’s The Shadow of the Crescent Moon challenges the mainstream narratives where the third world nations either have no representation or a negative presentation. Giving the voice to the voiceless, Bhutto’s fiction explicitly describes the narrative of the masses of FATA because, before that, we have only one dimension of narrative that is state’s narrative. For useful exploration and analysis, the idea of ‘repression and resistance’ will be discussed with reference to Louis Althusser’s ‘Ideology of State Apparatus’. For this purpose the primary text shall be deconstructed at all levels.